2022
DOI: 10.3389/fevo.2021.761147
|View full text |Cite
|
Sign up to set email alerts
|

Using a Novel Visualization Tool for Rapid Survey of Long-Duration Acoustic Recordings for Ecological Studies of Frog Chorusing

Abstract: Continuous recording of environmental sounds could allow long-term monitoring of vocal wildlife, and scaling of ecological studies to large temporal and spatial scales. However, such opportunities are currently limited by constraints in the analysis of large acoustic data sets. Computational methods and automation of call detection require specialist expertise and are time consuming to develop, therefore most biological researchers continue to use manual listening and inspection of spectrograms to analyze thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…As a seminal example, the falsecolour spectrogram for longdurations proposed by Towsey et al (2014) enabled users to identify species in large audio datasets and intuitively grasp the changes in dynamics of the acoustic signals by showing the spectrogram coloured according an acoustic index, which reflects the specific properties of the species vocalizations. Brodie et al (2022) further explored the efficacy of using falsecolour spectrograms to identify multiple frog species in longduration recordings and obtained data on the chorusing activity of the frog community. They found that frog choruses of different species could be visually identified with high accuracy in falsecolour spectrogams based on acoustic indices after a training phase.…”
Section: Discussionmentioning
confidence: 99%
“…As a seminal example, the falsecolour spectrogram for longdurations proposed by Towsey et al (2014) enabled users to identify species in large audio datasets and intuitively grasp the changes in dynamics of the acoustic signals by showing the spectrogram coloured according an acoustic index, which reflects the specific properties of the species vocalizations. Brodie et al (2022) further explored the efficacy of using falsecolour spectrograms to identify multiple frog species in longduration recordings and obtained data on the chorusing activity of the frog community. They found that frog choruses of different species could be visually identified with high accuracy in falsecolour spectrogams based on acoustic indices after a training phase.…”
Section: Discussionmentioning
confidence: 99%
“…See Section 6. Rapidly visualising large data sets to facilitate qualitative interpretation. For example, false‐colour spectrograms can condense years of data into a single plot, which permits identification of dominant soundscape patterns and seasonal changes (Brodie et al, 2022; Phillips et al, 2018; Towsey et al, 2018; Towsey, Zhang, et al, 2014). Detecting strong temporal and spatial trends, aiding identification of large‐scale soundscape patterns and areas of acoustic interest (e.g.…”
Section: Identifying Your Paradigmmentioning
confidence: 99%
“…Wider testing has demonstrated that associating acoustic indices with biodiversity metrics, such as species richness, diversity or abundance, is not straightforward. There has been some success in linking acoustic indices to the presence of individual species (Brodie et al, 2022; Papin et al, 2019; Towsey et al, 2018; Znidersic et al, 2020), or to broader taxon richness (Allen‐Ankins et al, 2023; Bradfer‐Lawrence et al, 2020; Dröge et al, 2021; Roca & Van Opzeeland, 2020). However, there are contradictory patterns reported in the literature.…”
Section: Identifying Your Paradigmmentioning
confidence: 99%